Evaluasi Performansi Sistem Terminal Peti Kemas Di Belawan Internasional Container Terminal PT. Pelabuhan Indonesia I (Persero) Dengan Metode Simulasi - Hadi Purwanto; Azalia Syahra (Fakultas Teknik Universitas Samudra, 2019)
The performance of container loading and unloading equipment may affect the performance of service system in internasional container barrier containers. The number of container and high inter arrival time with a small amount of equipment will cause in certain processes. The analysis of the system is done by simulation method wich can give an idea of the performance of container loading and unloading equipment at Belawan Internasional Container (BICT) with quickly and can predict system capability in providing service. The output produced is showing the performance of container terminal system that is produced service system is during 42,3284 hours and servive time on simulation of import system is for 28, 7468 hours. From the output of the performance of the system can be evaluated, that can be know in the export of queue in the process of preparation of containers in Container yards